2020
DOI: 10.3389/fpsyg.2020.01288
|View full text |Cite
|
Sign up to set email alerts
|

Processing Code-Switches in the Presence of Others: An ERP Study

Abstract: Code-switching is highly socially constrained. For instance, code-switching is only felicitous when those present are fluent in both languages. This means that bilinguals need to dynamically adjust their language control and expectation of code-switching to the current social situation or context. The aim of the present EEG study was to investigate how and when language control in the comprehension of code-switches is affected by the assumed language knowledge of others in the context. Spanish-English bilingua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 66 publications
1
35
1
Order By: Relevance
“…Moreover, we report a broadly distributed and extended LPC for the code-switched conditions. The LPC has now been documented in several studies on code-switching (e.g., Moreno et al, 2002Moreno et al, , 2008Ng et al, 2014;Ruigendijk et al, 2016;Beatty-Martínez and Dussias, 2017;Litcofsky and Van Hell, 2017;Fernandez et al, 2019;Kaan et al, 2020). While Moreno et al initially interpreted this component as reflective of processing an improbable or unexpected event, Van Hell and colleagues have suggested that it instead points toward sentence-level reanalysis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we report a broadly distributed and extended LPC for the code-switched conditions. The LPC has now been documented in several studies on code-switching (e.g., Moreno et al, 2002Moreno et al, , 2008Ng et al, 2014;Ruigendijk et al, 2016;Beatty-Martínez and Dussias, 2017;Litcofsky and Van Hell, 2017;Fernandez et al, 2019;Kaan et al, 2020). While Moreno et al initially interpreted this component as reflective of processing an improbable or unexpected event, Van Hell and colleagues have suggested that it instead points toward sentence-level reanalysis.…”
Section: Discussionmentioning
confidence: 99%
“…Boudewyn & Carter, 2018a). Similarly, a recent study demonstrated that the LPC (Moreno et al, 2002)-an ERP component typically found when bilinguals parse a code-switch and reflective of reanalysis or unexpectedness-is reduced when a bilingual participant parses code-switches in the presence of another bilingual interlocutor as compared to a monolingual interlocutor (Kaan et al, 2020). This suggests that bilingual processing demands are modulated by the pragmatics of a linguistic context (a state) and that cognitive (or attention) control operations may fluctuate on the basis of interlocutors' expected shared knowledge.…”
Section: Future Directions For a States Approach To Bilingualismmentioning
confidence: 89%
“…By extension, the type of discourse situation (e.g., code-switching vs. not; communicating with a group member vs. not) may also modulate how much pressure is placed and the extent to which the hippocampus contributes to a linguistic process like common-ground assessment. As before, however, relationships between bilingual experience and cognitive performance should be investigated based on well-developed linking assumptions (e.g., the pragmatic effects sketched above in Kaan et al, 2020). Alongside these possible approaches, we echo others in calling for clear reporting of the context in which bilingual testing occurs, given the effects of interactional context and particular language experiences (de Bruin, 2019;Luk & Bialystok, 2013;Whitford & Luk, 2019).…”
Section: Future Directions For a States Approach To Bilingualismmentioning
confidence: 94%
“…Aspects of individual speaker experience and the social context in which communication arises also influence the tendency to codeswitch (e.g., Beatty-Martínez, Navarro-Torres, Dussias, Bajo, Guzzardo Tamargo & Kroll, 2019; Declerck & Philipp, 2015; Fricke et al, 2016; Shen et al, 2020; Valdés Kroff et al, 2017). When preparing a response, bilinguals are sensitive to a host of less purely lexical factors such as the language proficiency of the other speaker (Kaan, Kheder, Kreidler, Tomić & Valdés Kroff, 2020; Kapiley & Mishra, 2019), the social context including the conventions for codeswitching in a particular community (Valdés Kroff et al, 2017) and aspects of status (Tenzer & Pudelko, 2015). Although power relations are less likely to play a prominent role across variable online codeswitching contexts (Barasa, 2016), it now seems that an account of switching based solely on cognitive factors and the conditions that give rise to difficulties suppressing words in the non-target language needs to encompass opportunity-specific aspects of socially complex language use.…”
Section: Introductionmentioning
confidence: 99%